L'ús comercial de la costa marítima d'Oriola: edició i notes onomàstiques i lingüístiques sobre el text d'un plet amb la ciutat d'Alacant (1643). - ABAT, BRAULI MONTOYA (Scripta, 2013)
This work consists on the philological edition of a text of 1643 and its onomastic and linguistic study. The document includes a series of statements about the ancient right of the city of Oriola/Orihuela to the commercial use of the stretch of coast that belongs to its term; this is the result of a dispute with the city of Alacant/Alicante, which denies the right of Oriola/Orihuela to use its waterfront to this effect. The reference to the watchtowers that existed in the coastal referred portion gives an interesting information about the existing names, whose evolution can be followed until today. The analysis of the text focuses on observing which use is done of the features that have been characterized in previous studies as oriolans properly, especially in the case of the Castilian meanings of the verb llevar ('to carry, to bring') in contrast to the ones of portar ('to bring').